9m-3m(m+6)=2(m+1)

Simple and best practice solution for 9m-3m(m+6)=2(m+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9m-3m(m+6)=2(m+1) equation:


Simplifying
9m + -3m(m + 6) = 2(m + 1)

Reorder the terms:
9m + -3m(6 + m) = 2(m + 1)
9m + (6 * -3m + m * -3m) = 2(m + 1)
9m + (-18m + -3m2) = 2(m + 1)

Combine like terms: 9m + -18m = -9m
-9m + -3m2 = 2(m + 1)

Reorder the terms:
-9m + -3m2 = 2(1 + m)
-9m + -3m2 = (1 * 2 + m * 2)
-9m + -3m2 = (2 + 2m)

Solving
-9m + -3m2 = 2 + 2m

Solving for variable 'm'.

Reorder the terms:
-2 + -9m + -2m + -3m2 = 2 + 2m + -2 + -2m

Combine like terms: -9m + -2m = -11m
-2 + -11m + -3m2 = 2 + 2m + -2 + -2m

Reorder the terms:
-2 + -11m + -3m2 = 2 + -2 + 2m + -2m

Combine like terms: 2 + -2 = 0
-2 + -11m + -3m2 = 0 + 2m + -2m
-2 + -11m + -3m2 = 2m + -2m

Combine like terms: 2m + -2m = 0
-2 + -11m + -3m2 = 0

Factor out the Greatest Common Factor (GCF), '-1'.
-1(2 + 11m + 3m2) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(2 + 11m + 3m2)' equal to zero and attempt to solve: Simplifying 2 + 11m + 3m2 = 0 Solving 2 + 11m + 3m2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 0.6666666667 + 3.666666667m + m2 = 0 Move the constant term to the right: Add '-0.6666666667' to each side of the equation. 0.6666666667 + 3.666666667m + -0.6666666667 + m2 = 0 + -0.6666666667 Reorder the terms: 0.6666666667 + -0.6666666667 + 3.666666667m + m2 = 0 + -0.6666666667 Combine like terms: 0.6666666667 + -0.6666666667 = 0.0000000000 0.0000000000 + 3.666666667m + m2 = 0 + -0.6666666667 3.666666667m + m2 = 0 + -0.6666666667 Combine like terms: 0 + -0.6666666667 = -0.6666666667 3.666666667m + m2 = -0.6666666667 The m term is 3.666666667m. Take half its coefficient (1.833333334). Square it (3.361111114) and add it to both sides. Add '3.361111114' to each side of the equation. 3.666666667m + 3.361111114 + m2 = -0.6666666667 + 3.361111114 Reorder the terms: 3.361111114 + 3.666666667m + m2 = -0.6666666667 + 3.361111114 Combine like terms: -0.6666666667 + 3.361111114 = 2.6944444473 3.361111114 + 3.666666667m + m2 = 2.6944444473 Factor a perfect square on the left side: (m + 1.833333334)(m + 1.833333334) = 2.6944444473 Calculate the square root of the right side: 1.641476301 Break this problem into two subproblems by setting (m + 1.833333334) equal to 1.641476301 and -1.641476301.

Subproblem 1

m + 1.833333334 = 1.641476301 Simplifying m + 1.833333334 = 1.641476301 Reorder the terms: 1.833333334 + m = 1.641476301 Solving 1.833333334 + m = 1.641476301 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1.833333334' to each side of the equation. 1.833333334 + -1.833333334 + m = 1.641476301 + -1.833333334 Combine like terms: 1.833333334 + -1.833333334 = 0.000000000 0.000000000 + m = 1.641476301 + -1.833333334 m = 1.641476301 + -1.833333334 Combine like terms: 1.641476301 + -1.833333334 = -0.191857033 m = -0.191857033 Simplifying m = -0.191857033

Subproblem 2

m + 1.833333334 = -1.641476301 Simplifying m + 1.833333334 = -1.641476301 Reorder the terms: 1.833333334 + m = -1.641476301 Solving 1.833333334 + m = -1.641476301 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1.833333334' to each side of the equation. 1.833333334 + -1.833333334 + m = -1.641476301 + -1.833333334 Combine like terms: 1.833333334 + -1.833333334 = 0.000000000 0.000000000 + m = -1.641476301 + -1.833333334 m = -1.641476301 + -1.833333334 Combine like terms: -1.641476301 + -1.833333334 = -3.474809635 m = -3.474809635 Simplifying m = -3.474809635

Solution

The solution to the problem is based on the solutions from the subproblems. m = {-0.191857033, -3.474809635}

Solution

m = {-0.191857033, -3.474809635}

See similar equations:

| -5(-2t+-8)= | | 2.5x-5+8=19.5 | | 0.5n-6=12 | | -1.5x+y=1 | | -1.5+y=1 | | 5(6x-3)=3(8x+1) | | 15x=6y-9 | | -9+7k+8(7+10k)= | | 2(x-2)=x+3 | | y-1.5=1 | | 3x+2x+5=10(x+1) | | 891.25=x(7.5+4.75) | | 22+2s=10+5s | | 22+2s=1 | | -12=-2h+4-1.2h | | 3x-5x+6=12 | | 2(2x-14)=x+2 | | 5x+5=11x+15 | | 2m+45=-23 | | 6+5=0 | | 8(s+3)=7 | | -3(-4+4h)= | | 53x+14=43x+36 | | 30x=27x+11 | | 3w+116=500 | | 2(x+2)=x+10 | | x=10/0 | | 3(a-2)=4b+5 | | 3+-3(-2h+6)= | | 104=4(2-4x) | | x+41=70 | | 6[5-8(-4)]+12=x |

Equations solver categories